Bilateral asymmetries in professional cyclists during a Grand Tour - Javaloyes, A.; Mateo-March, M.; Carpes, F. P.; Moya-Ramon, M.; Lopez-Grueso, R.; Zabala, M. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Pedalling asymmetries are a topic of interest to cycling coaches and athletes due to a potential link with performance and injury prevention. OBJECTIVES: The aim of this study is to describe the bilateral asymmetry of professional cyclists during two editions of a Grand Tour. METHODS: Here we set out to determine the power balance (power produced by each lower limb) between stronger and weaker leg (dominant vs. non-dominant) of 12 UCI professional cyclists competing at two Giro d`Italia editions. Power data were recorded during competition stages. Further analysis considered power data clustered into individual intensity zones (from Z1 to Z7). RESULTS: Higher intensity elicited better power balance (lower asymmetry) regardless of the stage profile. Intensity distribution analysed according to the role of the cyclist was lower for climbers in Z2 (p= 0.006) and Z7 (p= 0.002) and higher in Z5 (p= 0.023) compared to team helpers. Power balance ranged from 0 to 9 % across the different athletes. CONCLUSIONS: Increase in power output improves power balance, especially in team helpers, and the lower power balance at lower exercise intensities, which are most of the race time, may elicit significant cumulative loading on a given leg of the cyclists, which requires further attention regarding risks of overuse injury.